2017
DOI: 10.1016/j.amepre.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Parental Support for Age-based Indoor Tanning Restrictions

Abstract: Introduction Regulatory agencies, including the U.S. Food and Drug Administration, are considering policies to ban indoor tanning for youth aged <18 years. Using data from a nationally representative sample, this study assessed parental support for age-based bans as well as less restrictive parental permission requirements. Methods Data came from an online survey completed by 1,244 parents of adolescents aged 11–17 years. Weighted multivariable logistic regression models assessed correlates of supporting an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Data for our study came from the Adolescent Cancer Prevention Communication Survey, which was a national survey of parents of adolescents ages 11-17; the survey included items for the present study, as well as items for a series of other studies related to HPV vaccination and skin cancer prevention. [29][30][31] Participants were members of GfK's KnowledgePanel, a probability-based, online panel designed to be representative of adults living in US households. 32 This standing online panel is constructed via random digit dialing and probabilistic, address-based sampling to cover households with and without landline telephones.…”
Section: Participants and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Data for our study came from the Adolescent Cancer Prevention Communication Survey, which was a national survey of parents of adolescents ages 11-17; the survey included items for the present study, as well as items for a series of other studies related to HPV vaccination and skin cancer prevention. [29][30][31] Participants were members of GfK's KnowledgePanel, a probability-based, online panel designed to be representative of adults living in US households. 32 This standing online panel is constructed via random digit dialing and probabilistic, address-based sampling to cover households with and without landline telephones.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…33 Additional details about the overall survey have been reported previously. [29][30][31] In this study, eligible respondents were parents who reported never having talked to their child's healthcare provider about HPV vaccination. We focused on these parents to understand the perspectives that providers are most likely to encounter when they first broach the topic of HPV vaccination.…”
Section: Participants and Proceduresmentioning
confidence: 99%